A Fast and Activatable Cross‐Linking Strategy for Hydrogel Formation. (23rd December 2014) - Jonker, Anika M.; Borrmann, Annika; van Eck, Ernst R. H.; van Delft, Floris L.; Löwik, Dennis W. P. M.; van Hest, Jan C. M.
<x xml:space="preserve">Abstract</x> Strain‐promoted oxidation‐controlled cyclooctyne‐1, 2‐quinone cycloaddition (SPOCQ) is a fast and activatable cross‐linking strategy for hydrogel formation. Gelation is induced by oxidation, which is performed both chemically using sodium periodate and enzymatically using mushroom tyrosinase. Due to the fast reaction kinetics, SPOCQ‐formed hydrogels can be functionalized in one‐pot with an azido‐containing moiety using SPAAC cross‐linking. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>